Corporalidade e musicalidade na poética do estrangeiro do Farm in the cave: inspirações brasileiras no espetáculo The theatre - Juliana Macedo Carneiro (2013)
This dissertation aims at showing how the body-voice understood as the expressive totality of the actor and musicality are essential to the reception of codes that arise from foreign culture in the physical theater proposed by czech group Farm in the Cave. Through this work I analyze the recurring creative procedures in the spectacles (between 2002 and 2010) that were created from the contact with different cultural contexts. I analyze further the creative process of the play The Theatre, featuring the elements used in stage composition inspired by movement and musical patterns from brazilian rituals and cultural manifestations, seeking to identify which images they choose to highlight in staging and the cultural links that are established in the light of intercultural theories on theater.